2020
DOI: 10.3390/medicina56120648
|View full text |Cite
|
Sign up to set email alerts
|

Nurses Training and Capacitation for Palliative Care in Emergency Units: A Systematic Review

Abstract: Background and objectives: Palliative care (PC) prevents and alleviates patients´ suffering to improve their quality of life in their last days. In recent years, there has been an increase in visits to the emergency services (ES) by patients who may need this type of care. The aims were to describe the training and capacitation of nurses from ES in PC. Accordingly, a systematic review was performed. Materials and Methods: Medline, Scopus, and Cumulative Index to Nursing and Allied Health Literature (CINAHL) da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
(53 reference statements)
1
6
0
Order By: Relevance
“…The participants, especially in the ICU, experienced the period of transition of patients from curative intention of care to palliative care, and later end‐of‐life care, as stressful. This is in line with previous research (Thorn & Uhrenfeldt, 2017 ) and underscores the need for targeted education and training (Romero et al, 2020 ; Thorn & Uhrenfeldt, 2017 ). Definitions of palliative care (Radbruch et al, 2020 ; WHO, 2018 ) leave room for interpretation; the WHO emphasizes palliative care as an approach, early in a disease trajectory as well as at the end of life, whereas the International Association for Hospice and Palliative Care focuses on health‐related suffering related to persons with severe illness.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The participants, especially in the ICU, experienced the period of transition of patients from curative intention of care to palliative care, and later end‐of‐life care, as stressful. This is in line with previous research (Thorn & Uhrenfeldt, 2017 ) and underscores the need for targeted education and training (Romero et al, 2020 ; Thorn & Uhrenfeldt, 2017 ). Definitions of palliative care (Radbruch et al, 2020 ; WHO, 2018 ) leave room for interpretation; the WHO emphasizes palliative care as an approach, early in a disease trajectory as well as at the end of life, whereas the International Association for Hospice and Palliative Care focuses on health‐related suffering related to persons with severe illness.…”
Section: Discussionsupporting
confidence: 91%
“…The discourse aiming to broaden the scope of palliative care for everyone, irrespective of diagnosis and disease trajectory, may lead to a shift in how palliative care is viewed. However, at present, the expectations are that RNs have a general knowledge of palliative care in different contexts and that they are able to instigate palliative care interventions according to patients' needs, is a previously identified challenge (Romero et al, 2020 ). The question of how to translate and operationalize palliative care into clinical practice remains unanswered, although it is obvious that to ensure care quality at the end of life in acute care settings, the RNs' needs for education and training must be addressed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, it has been shown that some nurses possess theoretical knowledge in PC, but do not apply it in their clinical practice [10,27]. This justifies the recommendation for specific training for groups and specific health areas, aimed at the development of nursing competencies that will modify attitudes and favor the applicability of knowledge [12,28]. Furthermore, although the current trend is towards online training, some authors defend the need for face-to-face training, learning with simulation or case resolution, and discussion groups, which support the transfer of knowledge to behavior in care [11,27,27,29,30].…”
Section: Introductionmentioning
confidence: 99%